Species diversity of the freshwater red algal genus Kumanoa in Taiwan with the description of two new species: Kumanoa taiwanensis sp. nov. and Kumanoa yuanyangensis sp. nov. - Aristya, Ganies Riza; Chang, Wun-Ruei; Fontana, Silvia; Necchi, Orlando [UNESP]; Liu, Shao-Lun (Taylor & Francis, 2022)
The genus Kumanoa is the most species-rich group in freshwater red algae. Only one species, K. mahlacensis, has been reported in Taiwan. Here, we described two new species, K. taiwanensis and K. yuanyangensis. Based on rbcL and cox1, K. taiwanensis differs from its sister lineage (K. curvata and K. intorta, both endemic to China) by 3.7%–3.9% and 6.6%, while K. yuanyangensis differs from its sister species, K. vittata (endemic to Australia), by 2.9% and 8.2%. These genetic differences exceed the threshold of species boundary in Kumanoa, supporting their establishment as new species. The two new species proposed are also supported by three algorithmic species delimitation methods (i.e. ABGD, SPN and GMYC). In addition to molecular evidence, K. taiwanensis can be morphologically distinguished from K. intorta and K. curvata by having carposporophytes embedded in the whorl radius, monosporangia on the fascicles but not on the involucral filaments, and the lack of bisporangia. Kumanoa yuanyangensis can be morphologically differentiated from K. vittata by having barrel-shaped whorls and spermatangia on the regular fascicles but not on the short, specialized fascicles. Comparing the three Taiwanese species, K. mahlacensis and K. taiwanensis are dark green or blue green in colour and occur in warm alkaline environments, reflecting their close phylogenetic affinity. In constrast, Kumanoa yuanyangensis is dark red-brown in colour, lacks monosporangia and occurs in a cold and acidic environment. This study expands the known diversity of Kumonoa and sheds light onto their biogeography.
Keywords: cox1; Cryptic species; Morphology; rbcL; Species delimitation